(untitled) (Web of Teachers: Inderscience Research, 2024)
This article aims to study the main aspects of improving the organization of state financial control, focusing on strategies, initiatives and best practices that help to optimize the functions of state financial control. By examining the latest trends in supervisory principles, audit methodology, and anti-corruption measures, we aim to provide insight into how countries can strengthen their financial oversight systems to meet the demands of the modern governance landscape.